Social Impact Bonds and Socially Responsible Public Procurement in the 21st Century - Lamprinidis, Lampros (Journal of Public Policy and Administration, 2023)
Purpose: Socially Responsible Public Procurement is an important tool to support both Social Economy Organisations and wider public policies. The object of this paper is to examine the financial instrument of Social Impact Bonds (SIBs) by the Public Administration in order to support on the one hand sustainable development and social integration and on the other hand the Social Economy Bodies in their efforts to secure resources to achieve their mission (sustainable and socially inclusive development). Through the presentation of case studies, stakeholders will be able to understand the importance of Socially Responsible Public Procurement and the importance of Social Impact Bonds in ensuring an inclusive and environmentally respectful society. Methodology: Concise review of the theory of Social Impact Bonds and the connection with the Public Procurement through representative case studies from UK, USA and Israel. Findings: Presents the results that the utilization of social impact bonds had for contracting authorities, the development of the Social Economy and wider public policies (such as employment, social inclusion, etc.) Unique Contribution to Theory Practice and Policy: Through this paper, stakeholders will have the chance to understand the importance of SIB in relation to Socially Responsible Public Procurement. SIB is a new financial tool which can financially support Social Economy Bodies in order to fulfill their missions, but it also has disadvantages. The specific article includes proposals in order to improve the institutional framework of Social Impact Bonds.